Accountability after Nuclear War: Why Not Plan Ahead?. Issue 1 (2nd January 2020) - Perkovich, George
ABSTRACT: If nuclear war occurs, non-belligerents want the conductors to take responsibility for providing assistance to deal with harm imposed on them. This harm could take the form of radioactive fallout, climatic change that causes global food shortages and refugee crises. But states and experts preoccupied with winning (or at least not losing) wars that could go nuclear have largely ignored questions of post facto accountability. Nuclear-armed states claim to be responsible, defensive actors; therefore, they should not object if others demand processes to adjudicate the conduct of nuclear war after the fact and provide reparations and remedies to victims in non-belligerent nations. Indeed, international efforts to establish such accountability could strengthen deterrence against aggression and use of nuclear weapons.